CO2FIX V 3.1 - A modelling framework for quantifying carbon sequestration in forest ecosystems - Schelhaas, M.J.; Esch, P.W. van; Groen, T.A.; Jong, B.H.J. de; Kanninen, M.; Liski, J.; Masera, O.; Mohren, G.M.J.; Nabuurs, G.J.; Palosuo, T.; Pedroni, L.; Vallejo, A.; et al. (ALTERRA, 2004)
This report describes the conceptual approach of the CO2FIX V 3.1 model, as well as its implementation and numerous examples. This stand level simulation model is a tool which quantifies the C stocks and fluxes in the forest biomass, the soil organic matter and the wood products chain. Included are also a bioenergy module, a financial module and a carbon accounting module. The model is applicable to many different situations: afforestation projects, agroforestry systems, and selective logging systems. The model is freely available from the web, together with numerous examples.